The return to firm investment in human capital - Rita Almeida; Pedro Carneiro (Centre for Microdata Methods and Practice (cemmap), 2005)
In this paper we estimate the rate of return to firm investments in human capital in the form of formal job training. We use a panel of large firms withun usually detailed information on the duration of training, the direct costs of training, and several firm characteristics such as their output,workforce characteristics and capital stock. Our estimates of the return to training vary substantially across firms. On average it is - 7% for firms not providing training and 24% for those providing training. Formal job training is a good investment for many firms and the economy, possibly yielding higher returns than either investments in physical capitalor investments in schooling. In spite of this, observed amounts of formal training are very small.
Keywords: C23; D24; J31; 330; On-the-Job Training; Panel Data; Production Function; Rate of Return; Bildungsinvestition; Humankapital; Betriebliches Bildungsmanagement; Return on Investment; Großunternehmen; Panel